History of the administration of psychedelics in France - Dubus, Zoe; Grandgeorge, Elise; Verroust, Vincent (Frontiers in Psychology, 2023)
This article reviews the historical protocols for the administration of “classic” psychedelics in France, from the 1920s to the 1960s. Taking a chronological approach, it investigates the way mescaline, LSD, and psilocybin were administered, the subjects involved, the route of administration, the dosage, and the epistemological context of the research. From the 1930s, the Sainte-Anne school dominated French experimentation with psychedelics, inserting these studies on “hallucinogens” into a biological conception of therapeutics, where the notion of “shock” dominated. The sessions show particularly anxious experiences, sometimes described as “torture” by the patients who underwent them. With just a few rare cases of recovery reported, these substances were not considered as medicines, but rather as tools for exploration in the context of experimental research; thought of not as psychedelics (“mind manifesters”) but as psychodysleptics (“mind disruptors”). While these tools could be useful for the diagnosis of sick patients, French physicians did not manage to demonstrate clear therapeutic benefits in the use of psychedelics, perhaps because of their reluctance, in most cases, to determine an optimum dose, and also very often to appreciate the context of administration and the relationship with the patient. This article allows us to understand the reasons for the therapeutic failures reported by these early French psychedelic researchers, but also to help explain the current reluctance of French health professionals who in the face of the “psychedelic renaissance” remain strongly influenced by the very negative early representations of these substances.